Institutional Mechanism of Engineering Istisna and Prospects for Its Use in Saudi Arabia - Danylina, Svitlana; Grimalyuk, Andrei (Journal of King Abdulaziz University: Islamic Economics, 2025)
The article raises the problem of neo-industrial diversification of Saudi Arabia using the institutional mechanism of engineering istisna. The article shows that Saudi Arabia has all the objective and subjective conditions for the successful creation of a neo-industrial model of the information society in the process of the fourth industrial revolution. A balanced institutional approach is used to analyze this problem, which assumes the unity and interrelation of institutional and technological changes in the process of neo-industrial diversification in Saudi Arabia. The authors conclude that the institute of engineering istisna will allow Saudi Arabia to organize the creation of "smart", automated neo-industrial enterprises by orders of private investors. Thanks to this institutional mechanism, Saudi Arabia in the historical perspective can become the world leader in the controlled process of the fourth industrial revolution, just as England became the leader of the spontaneous process of the first industrial revolution more than two hundred years ago.